Clinical Manifestation of Childhood Diphtheria - Geune Putroe Zulfan; Jumaini Adriana Sihombing; Desrinawati Muhammad Amin; Aninda Dinar Widiantari; Monalisa Putri Eka Berti; Farida Murtiani (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
Even though diphtheria vaccination has been routinely done all around the world, some of developing country still reported outbreak. Indonesia declared diphtheria outbreak in 2017. Diphtheria is characterized by sore throat, fever and the formation of pseudo-membrane located in the tonsils, pharynx or nasal cavity. Diphtheria is very common in children. This study was conducted to determine the clinical picture of diphtheria in children at Sulianto Saroso Infectious Disease Hospital January 2018 - December 2018. The study was descriptive cross – sectional using medical records of diphtheria patients for the period January 2018 – December 2018. The sample is 141 diphtheria patients with the total sampling method. Data analysis using univariate. In this study, out of 141 children with diptheria, the highest number of cases was recorded boy (58,2%), among 6-11 years old, and fully vaccinated (60.3%). Most patient complained about sore throat (95%), fever (93.6%), and bullneck (32.6%). Majority of diphtheria patients with bilateral tonsillar membranes were also found (71.6%), followed by the majority of negative culture results (66.7%), experienced no complications (78.7%), and discharge (99.3%). Clinical characteristic that commonly appeared were sore throat, fever, and bilateral tonsillar membrane. We found it is important to diagnose and treat early to prevent complication and mortality.